Desenvolvimento de um simulador para acesso vascular ecoguiado de baixo custo para o treinamento de médicos em ambiente hospitalar - Gomes, Sergio Vitasovic (2024)
Introduction: The ultrasound-guided vascular access requires technical knowledge concerning the ultrasound handling, coupled with manual skills and movements' coordination, which enable the doctor to correctly execute the technique. Objective: To develop a low-cost, easily reproducible simulator for ultrasound-guided vascular access, which mimics the ultrasonographic characteristics of human tissue. Utilize it in a training workshop for residents at Hospital Ipiranga. Methodology: It was conducted cross-sectional, descriptive, and exploratory study in which we outlined the creation of a ballistic gel-based model for ultrasound-guided puncture. Subsequently, a training course was provided on ultrasound-guided puncture using the developed model. The participating residents completed a pre-test, watched a video lecture, participated in a training workshop, and completed a post-test afterward. Results: It was possible to develop a low-cost model that accurately reproduces the ultrasound characteristics of human tissue. The workshop proved effectiveness in reinforcing the acquired theoretical knowledge and in boosting participants' confidence while performing the procedure. Discussion: Teaching this technique is often overlooked in both undergraduate and postgraduate education. Incorporating active learning with flipped classroom methods, coupled with practical workshops, enhances participants' self- confidence, and perhaps, a continuous education program on the subject could be the best way to disseminate this knowledge.